Park Square, ca. 1925 - Lawrence, George E. (Tufts Archival Research Center, 2005)
Street-level view of partially demolished buildings located at Park Square. Signage adorns the facade of the building. A large construction vehicle is visible in front of the buildings, and debris fills the street. Three men are included in the photograph. 7 1/4 x 9 1/3 Photographs